FIGURE 3 in The genus Callitriche (Plantaginaceae: Callitricheae) in South America - Lansdown, Richard V.; Hassemer, Gustavo (Zenodo, 2021)
FIGURE 3. Epitype of Callitriche antarctica (R.C. Winkworth & F. Hennion 42, P barcode P02432590). Copyright: Muséum National d'Histoire Naturelle. : Published as part of Lansdown, Richard V. & Hassemer, Gustavo, 2021, The genus Callitriche (Plantaginaceae: Callitricheae) in South America, pp. 85-118 in Phytotaxa 501 (1) on page 90, DOI: 10.11646/phytotaxa.501.1.3, http://zenodo.org/record/5424744